A Random Item Response Model of External Territorial Threat, 1816–2010. Issue 4 (18th July 2022) - Miller, Steven V
Abstract: Multiple scholars have shown that external territorial threat, conceptually the level of concern for a state that its territorial integrity is subject to violent conflict and imposed contraction by other states, has major implications for the state's domestic political environment. However, the strand of scholarship that agrees on the domestic political effects of external territorial threat disagrees on how to code this important concept. These works either rely on binary indicators that do a poor job communicating "increasing" or "decreasing" territorial threat or use dyad-year indicators of conflict propensities as a stand-in for a state-year-level observation. I use this research note to offer an empirical measurement of state-year external territorial threat from a Bayesian random item response model for all states from 1816 to 2010. I assess the face validity and construct validity of the data these models generate, all of which suggest the measure does well to capture the concept in question. I close with a statement of the availability of the data and their potential applications.